The Middle Jurassic palynology of the Sagres region, southern Portugal. - Borges, Marisa (2010)
The Algarve Basin corresponds to the southernmost geological province of mainland Portugal. It has an E-W strike and is represented onshore from Cap São Vicente to the Guadiana River on the Portuguese-Spanish border. More than 3000 m of essentially marine sediments accumulated during Mesozoic-Cenozoic times in the Algarve Basin.